A dança como prática pedagógica na educação física escolar - Almeida, Emily Cristina Pereira de (Universidade Federal do Tocantins, 2022)
The general objective of this study is to understand the pedagogical approach of dance in Physical Education in state schools in Tocantinópolis/TO, more specifically, to contextualize dance at school in dialogue with legal documents and academic production in the area; identify how the pedagogical intervention of dance occurs in Physical Education in state schools in Tocantinópolis and discuss the pedagogical practice of dance in the current context of school Physical Education. Therefore, a qualitative, exploratory, descriptive-interpretive research was carried out. For data collection, a semi-structured interview was used, which was applied to seven state teachers. The qualitative analysis of the data took place through a process of reading and categorization, considering the thematic approaches evidenced in the respondents' answers. It was found that teachers consider dance in their teaching practices and consider it important for the development of students at school. Along this path, we identified some challenges for teaching dance at school, such as the lack of experience of teachers, from initial training, the predominance of sport as a content of Physical Education at school, gender issues and the resistance of students. We conclude that, despite the limits, the approach to dance at school is linked to the concept of teaching and the way to conduct it with students. The continuous monitoring of the teacher and the encouragement of the student's protagonism proved to be favorable to pedagogical mediations with dance at school.